Investment in Emerging Markets We Are Not in Kansas Anymore ... Or Are We? - Magud, Nicolas (IMF Working Papers; Working Paper ;, 2015)
We document that (i) although private investment growth in emerging markets has decelerated in recent years, it came down from cyclical highs and remains close to pre-crisis trends; and (ii) investment-to-output ratios generally remain close to or above historical averages. We show that investment is positively related to expect future profitability, cash flows and debt flows, and negatively associated with leverage. Critically, it is also positively related to (country-specific) commodity export prices and capital inflows. Lower commodity export prices and expected profitability, a moderation in capital inflows, and increased leverage account for the bulk of the recent investment deceleration.